Evaluation of arterial blood gas analysis in diagnosis of neonatal hypoxic ischemic encephalopathy (动脉血气分析在诊断新生儿缺氧性脑病中的价值) - SHI Xiaoyan (史晓燕); LIU Yanlin (刘艳林) (Association of Integrative Nursing, 2021)
Objective To evaluate the arterial blood gas analysis of pH and lactic acid level in diagnosis of neonatal hypoxic ischemic encephalopathy (HIE). Methods To retrospectively analyzed the clinical data of 43 neonates with HIE. Neonates were divided into the normal-mild group (without brain injury) and moderate-severe group (with brain injury) according to results of head MRI and video-electroencephalography (VEEG). The arterial blood gas analysis of pH and lactic acid level of two groups were compared. The receiver operating curve (ROC) model was used to evaluate the pH and lactic acid level in diagnosis of HIE. The univariate analysis and multiple logistic regression analysis were used to analyze potential influencing factors of HIE. Results Neonates in the moderate-severe group(with brain injury) had a lower pH value and higher lactic acid level compared with those in the normal-mild group(without brain injury). The ROC analysis showed that the area-under-the-curve (AUC) of pH was 0. 656, with a sensitivity of 78. 0% and specificity of 53. 8%; the AUC of lactic acid level was 0. 877, with a sensitivity of 83. 3% and specificity of 82. 7%. The multiple logistic regression analysis showed that the increased lactic acid level was independent risk factor for brain injury in HIE neonates (OR=7. 504, P=0. 001). Conclusion Findings of the study showed that increased lactic acid was independent risk factor for brain injury in HIE neonates, and was a better index to predict HIE. (目的 探讨动脉血气分析pH和乳酸在诊断新生儿缺血缺氧性脑病(HIE)中的临床价值。方法 回顾性分析2018年1月-2020年9月江苏省苏北人民医院NICU收治入院的43例HIE患儿的临床资料, 根据头颅MRI和视频脑电图(VEEG)将HIE患儿分为正常/轻度异常组(无脑损伤组)和中重度异常组(脑损伤组)。分析2组患儿动脉血pH和乳酸水平差异, 应用受试者工作曲线(ROC)评价pH和乳酸对HIE的诊断价值, 采用单因素和多因素logistic回归分析影响HIE脑损伤的危险因素。结果 与无脑损伤组相比, 脑损伤组患儿的pH明显降低, 乳酸水平明显升高。ROC结果显示, pH的曲线下面积(AUC)为0. 656, 灵敏度为78. 0%, 特异度为53. 8%, 乳酸的AUC为0. 877, 灵敏度为83. 3%, 特异度为82. 7%。多因素logistic回归分析表明乳酸升高是HIE患儿脑损伤的独立危险因素(OR=7. 504, P=0. 001)。结论 头颅MRI和VEEG异常的HIE患儿动脉血pH和乳酸水平存在差异, 乳酸水平升高是HIE患儿脑损伤的独立危险因素, 可以作为预测HIE发生的良好指标。)